Audit of newborn screening programme for congenital hypothyroidism - Hussain, Suhaimi; Taib, Mai Nurul Ashikin; Zainol, Ahmad Rodzi (Japan International Cultural Exchange Foundation (JICEF), 2013)
Congenital hypothyroidism screening programme in Universiti Sains Malaysia (USM) was started since 2004 using cord blood TSH. An audit of the screening programme for a period of 24 months was done for the year 2010 and 2011. A total of 12928 newborn babies were screened with coverage of 100%. Two cases were confirmed to have primary congenital hypothyroidism. The mean recall rate was 2.31% and the mean sample rejection rate was 1.59%. The subject response for the repeat test was 63% for the year 2010 and 78% for the year 2011. Continuous surveillance is important to ensure the National Quality Assurance (QA) were met.